2018
DOI: 10.15244/pjoes/83693
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Assessment of Heavy Metals in Soils and Plants around a Molybdenum Mine in Central China

Abstract: Although environmental problems caused by metal mining have become increasingly prominent, the pollution by associated heavy metals is easily neglected. In general, molybdenum mines are lowgrade and hence the high level of associated heavy metals easily causes pollution in the surrounding areas. Here we investigated the total concentrations and forms of Mo and associated Cu, Cd, Pb, and Zn in soils under different land-use types (barren, wheat, rape, and apple-seedling fields) and different plants (cultivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…It is inevitable the long-term mining activity also caused the increase of Cu, Mn, and Zn in soil. Similar results have also been reported in the research of Han et al (2019), who found Mo mining could not only increase the Mo concentration, but also increase the concentrations of the associated heavy metals such as Cu, Pb, and Zn in Shaanxi Mo mine area. Mo concentration in the unexploited area was 108.13 mg kg −1 , 54.1 times higher than the background values ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is inevitable the long-term mining activity also caused the increase of Cu, Mn, and Zn in soil. Similar results have also been reported in the research of Han et al (2019), who found Mo mining could not only increase the Mo concentration, but also increase the concentrations of the associated heavy metals such as Cu, Pb, and Zn in Shaanxi Mo mine area. Mo concentration in the unexploited area was 108.13 mg kg −1 , 54.1 times higher than the background values ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…This result showed that long-term mining activity had led to the enrichment of Mo in soil, which agrees with the previous findings. Han et al (2019) confirmed that the Mo concentration reached 14.4 times the soil background value in Shaanxi Province because of the mining activity. Boojar & Tavakkoli (2011) demonstrated that Mo mining has resulted in a massive increase Mo concentration of soil and the mean concentration of Mo in the mining soil reached 448 mg kg −1 .…”
Section: Discussionmentioning
confidence: 55%
“…Mo uptake by plants depends mainly on Mo forms and concentrations in soils, which can be increased by human activities such as mining [8] and sludge applications [9]. In Mo-mining affected soils, Mo concentrations can reach up to 1071.52 mg/kg [10] and 2903.91 mg/kg [11], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there has been a progressive global increase in the amount of heavy metals in the environment (Chen et al 2015;Murtaza et al 2017;Han et al 2019). Such pollution from numerous heavy metals has become severe in many regions of China because of the rapid development of China's economy and rapid growth in the population in recent decades (Huang et al 2007;Wang et al 2011;Chen et al 2015;Han et al, 2019). In addition, a variety of heavy metals can be deposited into the same habitat (Wang et al 2011(Wang et al , 2019d(Wang et al , 2020cChen et al 2015;Han et al 2019;Jiang et al 2019) and can accumulate to high concentrations in some habitats (Motesharezadeh et al 2017;Murtaza et al 2017;Han et al 2019).…”
Section: Introductionmentioning
confidence: 99%